Revitalization with Stagnation: The Mixed Effects of Vietnam’s New Rural Development Program - Nguyen, Tuan Anh; Rigg, Jonathan (Journal of Political Sociology, 2025)
Based on research in four communes in rural areas of Hanoi, this paper investigates the hidden shortcomings of Vietnam’s New Rural Development program. Introduced in 2010, the program was designed to modernize farming, diversify rural economies, boost incomes, and reduce rural poverty. We argue that while headline data paint a positive picture, these achievements have been secured through an unsustainable combination of non-farm laboring, often ex situ, by younger generations and low return farm laboring, in situ, by older residents. These are socially combined – and make economic ‘sense’ – in the context of households that operate as units of production, reproduction and redistribution. With rice land abandonment and ageing farmers, the fissures in the New Rural Development program are becoming all too clear.